Melastoma malabathricum Linn attenuates complete freund's adjuvant-induced chronic inflammation in Wistar rats via inflammation response. Issue 1 (December 2016) - Kumar, Vikas; Bhatt, Prakash; Sharma, Kalicharan; Rahman, Mahfoozur; Patel, Dinesh; Sethi, Nikunj; Kumar, Atul; Sachan, Nikhil; Kaithwas, Gaurav; Al-abbasi, F.; Anwar, Firoz; Verma, Amita
Abstract Background Natural products use for arthritis treatment is gaining importance in the medical worldt. Various studies reports medical importance ofMelastoma malabathricum Linn . (MM ) (Melastomataceae), also known as "putki, " has a broad range of health benefits, for its free radical scavenging constituents. The current investigation scrutinizes the antioxidant and anti-inflammatory effect ofMM against adjuvant-induced arthritis in experimental rats. Methods High-performance thin layer chromatography (HPTLC) was used for estimation of phytochemical-constituents present in theMM extract. Protective effect ofMM extract in Wistar rats was estimated using CFA-induced model. The rats were divided into different groups with six rats in each group. All animals received oral administration ofMM and indomethacin for 28 days. The body weight and arthritic score were scrutinized at regular intervals. At the end of experimental protocol, the rats were sacrificed, and blood samples were used for antioxidant, hematological parameters, pro-inflammatory and inflammatory mediator, respectively. Histopathological observation was used to evaluate the protective effect ofMM extract. Result & discussion Current study confirmed the preventive effect ofMM against adjuvant-induced paw edema, paw redness and arthritic progression.MM significantly (P  < 0.001) modulated the oxidative stress parameters as well as hematological parameter induced by CFA. The result also altered the distorted level of proinflammatory mediators and inflammatory mediator, which further reinforce the implication ofMM in CFA induced arthritis. Histological analyses of joints of rats showed a reduction in the synovial hyperplasia and mononuclear infiltration in theMM treated group which provides evidence for the antiarthritic effect ofMM . Conclusion From above parameters our study states that theMM is capable of restraining the alteration produced via adjuvant-induced arthritis in aminals. The repressing effect ofMM could be attributed, at least in part, to antioxidant, hematological and anti-inflammatory effect. Graphical abstract Figure Caption:Melastoma Malabathricum Linn Attenuates Complete Freund's Adjuvant-Induced Chronic Inflammation in Wistar rats by Inflammation Response